How we vote : innovation in American elections - Hale, Kathleen; Brown, Mitchell (Public management and change., 2020)
"How We Vote uses the lens of public administration to examine the conduct of elections and the work of election officials as a contemporary intergovernmental enterprise. Kathleen Hale and Mitchell Brown explore how election officials are innovating to resolve the interconnected management, technological, and political challenges in the more than 8,000 election jurisdictions across the United States. This environment is complex not only because voting practices vary from state to state but because national officials, multiple government agencies, the judicial system, voting equipment vendors, nonprofit groups, and citizen activists also influence practices, boundaries, and possibilities for change. Each topical chapter is grounded in original data gathered from national, state, and local election officials and policymakers across the United States. The topical chapters analyze voter registration, voting options, improvements in voter convenience, support for voting in languages other than English, the integrity of the voting process, and voting system technology to offer a fascinating picture of how we vote now and will do so in the future. The solutions crafted by election administrators illuminate the process of public sector innovation and change"--Publisher's description.